Consumo voluntário e digestibilidade aparente da silagem de capim elefante (Pennisetum purpureum Shum)em diferentes idades de corte, em ovinos - Merith Yves Higashi Ribeiro (2011)
Our objectives were to determine the voluntary intake and digestibility of nutrients in the elephant grass silage in three cutting ages (56, 84 and 112 days old). We used 18 sheep breed with an average weight of 34.7 kg were held collections total feces and urine. The statistical design was completely randomized design with three treatments (cut time) and six replicates (sheep), the comparisons of means test conducted by the Student Newman Keuls (SNK) at 5% probability (p <0, 05). The consumption of dry matter (DM) for the age of 56 days was 97.78 g / MW / day, being superior in cutting age (p <0.05). digestibility of DM intake was observed mesmo.Os and digestibility of gross energy followed the same trend observed for MS. A significant reduction in digestible energy values with increasing age (p <0.05). The digestibility of crude protein (CP) were high on the cutting age of 56 and 84 days, being similar, and higher with 112 dias.Todos treatments showed positive nitrogen balance. The values found for the consumption of NDF were 60.9768, 56.6446 and 48.0347 g / MW / day for ADF intake were 37.4119, 34.2782 and 28.0398 g / MW / day for ages 56, 84 and 112 days respectively. According to the results of the elephant grass cut to 56 days produces an excellent quality silage and silage produced on the 84 days is of good quality and silage produced on the cut to 112 days is of limited quality.